Orientalists Attack Against Prophetic Traditions: Awareness and Wake up Call - Ahamad Faosiy Ogunbado; Ishaaq El-Mubarak (IJUS | International Journal of Umranic Studies, 2022)
Orientalists had been working seriously towards the demolition of the second primary source of Islamic law where most Islamic proofs are derived. Given the strong links between the unnecessary allegations against some Prophetic traditions and irrelevant arguments about the compilation of Sunnah clearly proves their sceptics around the entire words of the Holy Prophet Muhammad (Peace be upon him). With this regard, there is a pressing need to replace some assumptions and misconceptions regarding these standpoints through academic approaches, so that Muslims will not be discouraged and misguided away from the real sources of Islamic law. For this sake, this study seeks to establish a number of facts which can eliminate the doubtful mind Muslims might have assumed from the wrong perceptions this group had created around the compilation and validity of Sunnah. In addition to that, this article aspires to reveal Orientalist deceiving facts in swapping false theories into realities in Islam. It also tends to evaluate the group’s plan and see whether they really wish to support Islam with these agendas or demolish it. Moreover, do they have any sincere intention and objections in probing the authenticity of Sunnah? In achieving these goals, descriptive method is used to pinpoint techniques and features of this set of group. While analytical approach is adopted with the aim of acknowledging their strategies. Apparently, findings assert that Orientalists doesn’t have any reasonable justification in challenging the validity of the Prophetic tradition. Asides that, results show that this set of people are merely using this ideology to divert Muslims’ attention from the faithful belief they have for the Prophet and his traditions.